Development Of University Campus Wide Information System (UCWIS) Using Integrated GIS Map And Database Development. - S. Ahamad, Mohd Sanusi; Wan Hussin, Wan Muhd Aminuddin; Ahmad, Dr. Shamshad (Universiti Sains Malaysia, 2007)

(untitled)
The research is a mapping project effort to create a campus base map that will serve as a common reference for all spatial data on USM main campus and the Engineering campus.